EFEKTIVITAS PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA AUDIOVISUAL TERHADAP EFIKASI DIRI KEMANDIRIAN IBU NIFAS - junengsih, Junengsih; Oktalia, Juli; Kusumastuti, Ani; Dwi Wahyuni, Elly (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
The independence of postpartum mothers can be achieved if the midwifery care activities are based on good cooperation between midwives in providing knowledge and motivation to postpartum mothers in meeting their needs. What is very much needed in postpartum care is the provision of adequate and quality postpartum care. In such situations, the role of the midwife in assisting the health of the individual is very important. The aim of the research is to determine the effectiveness of health education using audiovisual media on the knowledge, attitudes, and behaviors of postpartum mothers' independence, so that postpartum mothers remain healthy in fulfilling their role as new mothers. Additionally, postpartum mothers can continue to perform their usual activities. This research method uses a quasi-experimental design with pre- and post-tests with a control group. The data collection technique was conducted through purposive sampling. The sample size for the study uses hypothesis testing for the difference in means between two independent groups. The data collection technique was carried out by purposive sampling. The sample size of the study used a hypothesis test of the average difference in two independent groups (Lameshow, 2001) so that the number of 30 treatment respondents and 30 control respondents was obtained. Data analysis used paired t-test and Independent t-test statistical tests. The results of the study showed an increase in knowledge, attitudes and behavior in controlling postpartum maternal hypertension in the intervention group. There was a significant difference in knowledge, attitudes and behavior in postpartum mothers about postpartum maternal independence between the intervention group and the control group after the intervention (p value: 0.000). Health education using audiovisual media for postpartum mothers about postpartum maternal independence can be replicated for use in various health service settings.